Equivalent Errors in the Text of the Grundrezept Gänsebraten Translation by Students Majoring In German Literature - Suprayitno, Wisda Nasikah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
This descriptive qualitative research aims to describe the forms of word equivalence errors in the translated text of a cooking recipe entitled Grundrezept Gänsebraten. The data source in this research is students from the Department of German Literature who had taken the Übersetzung course. The data in this study are words, phrases, and clauses that contain word equivalence errors by students. The data were obtained with the help of analysis tables, then analyzed by reading, identifying, classifying, and comparing it with the researcher's version of the translation which has previously been validated by a triangulator. Then the data was grouped by the types of errors and will be drawn to a conclusion. Based on the analysis of the translation of the recipe text with the title Grundrezept Gänsebraten by three students, seven differences between the translation and the translation suggested by the researcher were obtained. The differences include two errors at the word selection level, three errors at the phrase level, and two errors at the clause level.